POSISI PEREMPUAN KOTA CIREBON DI TINGKAT NASIONAL DAN JAWA BARAT - Falatehan, Sriwulan Ferindian; Maemunah, Maemunah (Universitas Wiralodra, 2020)
The gender equality is included in one of human rights as a human being. The right to live respectfully, free from fear can also be free to make choices in life. All of these rights are not only intended for men, but also have the same rights as men. As a result of the need to support the family and the increasing level of education of women, the emergence of the issue of gender inequality began to be voiced in Indonesia since the 1960s. This issue became part of the phenomena and dynamics of Indonesian society that made women's position more equal to men. This study intended to determine the condition and position of women in the city of Cirebon, weaknesses and strengths in the IPM (Human Development Index), IDG (Gender Empowerment Index), and IPG (Gender Development Index). This study uses the Normative Juridical approach, which is research with an approach that is more emphasized on secondary data in the form of primary, secondary or tertiary legal materials. Until now, the city of Cirebon in the empowerment of women shows quite successful achievements, namely rank 5 for IPM, rank 3 for IDG, and rank 3 for IPG at the level of West Java Province.